Tanggung Jawab Substitusi Pemerintah Daerah dalam Perspektif Onrechtmatige Overheidsdaad - Filza Rachma Hafizni; Yunita Ratna Sari (Indonesian Democracy Research Center, 2026)
This study aims to analyze the legal position of the DKI Jakarta Regional Government and to construct the juridical basis of substituted liability in unlawful act (tort) disputes arising from the Jakarta LRT Phase 1B project in Rawamangun. The research employs a normative legal method with statutory, conceptual, and case approaches to examine the relationship between the regional government and regional-owned enterprises (BUMD) as project implementers. The findings indicate that although direct liability formally rests with the BUMD, the regional government cannot be entirely absolved of legal responsibility, as the project constitutes a manifestation of public policy financed through the regional budget (APBD). Non-physical losses experienced by the community may be qualified as onrechtmatige overheidsdaad (unlawful government act), particularly when such losses stem from policy negligence or failure in impact mitigation. In such circumstances, liability may be attributed to the regional government through the concept of substituted liability (vicarious liability), especially when the BUMD is unable to fulfill compensation obligations. Furthermore, the study finds that litigation-based dispute resolution mechanisms are ineffective and inconsistent with the principles of good governance. Therefore, this study recommends strengthening non-litigation mechanisms through the establishment of an Independent Mediation Committee and the provision of a risk reserve fund as an operational form of substituted liability. This model is expected to ensure a faster, more transparent, and equitable dispute resolution process for affected communities.